EFEKTIVITAS MODEL GROUP INVESTIGATION DALAM MENINGKATKAN KEMAMPUAN BERBICARA PESERTA DIDIK SEKOLAH DASAR - Ramandha, Tasya; Saepurokhman , Asep; Sukmana, Ece (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Speaking skills are essential language competencies that play a vital role in daily life and form an integral part of Indonesian language learning in elementary schools. However, students speaking abilities remain low, with students being passive during interactions and lacking confidence. This condition occurs due to teacher-centered learning methods. This study aims to determine the process, results, and improvement of the speaking skills of fifth-grade elementary school students in North Sumedang District for the 2025/2026 academic year using the Group Investigation model. The method employed was a quasi-experiment with cluster random sampling, dividing the population of 122 students into three regional clusters: urban, semi-urban, and border schools, resulting in an effective sample size of 64 students. The research instruments included teaching modules, observation sheets, performance assessment tests, and learning motivation questionnaires. Data analysis was conducted using a non-parametric statistical approach through the Wilcoxon Signed-Rank Test via SPSS version 27. The data analysis results showed a value of -6,960 with a of -1,96, yielding the condition with a significance value of 0,000 < 0,05. This is further supported by the fact that all 64 students (100%) experienced a significant score increase with an average of 91 in the very good category. Therefore, the success level of speaking instruction through the Group Investigation model is high.